Space-time analisis of level infestation of the coffee-leaf-miner Leucoptera coffeella, (Guérin-Menèville & Perrottet, 1842) (Lepidoptera: Lyonetiidae) in an organic coffee (Coffea arabica L.) - Scalon, João Domingos; Silva Mateus, Ana Lúcia Souza; Zacarias, Mauricio Sergio (Coffee Science - ISSN 1984-3909, 2014)
The coffee leaf miner Leucoptera coffeella, (Guérin – Menèville & Perrottet, 1842) is a key pest in coffee plantations in Brazil. This pest is important because causes losses of up to 50% in the production of coffee, depending on the loss of area of the photosynthesis, as result of necrosis on the surface of the leaf. It is well known that the understanding of the spatial distribution of insects is important in the context of biological control of pests in organic production. So, the goal of this study is to use the methods proposed by Diggle et al. (1995) to analyze the spatial and temporal relationships of the intensity of infestation of the coffee-leaf-miner on an organic coffee plantation in training. For this work, it was collected, monthly, between June 2005 and March 2007, ten leaves from 35 points located in an area of one hectare of an organic coffee plantation (Coffea arábica L.). Once the number of mined lives was superior to 30%, the sample point was considered infested. To analyze the spatial and temporal relationships of the intensity of infestation of the coffee leaf miner in the plantation, we used an adaptation of Ripley’s K function. The method was able to identify clearly the absence of space-time interaction in the infestation of the coffee leaf miner and an evident cluster behavior in time. We conclude that the location of the infestation is independent of the month which it occurred.